2017
DOI: 10.3390/ma10080842
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Micro-Abrasive Wear in Coatings of TaC-HfC/Au for Biomedical Implants

Abstract: The object of this work was the deposition of a Ta-Hf-C thin film with a gold interlayer on stainless steel, via the physical vapor deposition (PVD) technique, in order to evaluate the properties of different systems subjected to micro-abrasive wear phenomena generated by alumina particles in Ringer's solution. The surface characterization was performed using a scanning electron microscope (SEM) and atomic force microscope (AFM). The crystallographic phases exhibited for each coating were obtained by X-ray dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…In the evaluated system (film-substrate), there is a cathodic reaction on the surface of the coating and an anodic reaction produced on the surface of the substrate. The results also show that the application of the BixSiyOz coating, imparts thermodynamic stability to the surface increasing the protection potential of the system 27,28 . Figure-7 shows the diffraction patterns, taken at an angle, for the coatings.…”
Section: Resultsmentioning
confidence: 74%
“…In the evaluated system (film-substrate), there is a cathodic reaction on the surface of the coating and an anodic reaction produced on the surface of the substrate. The results also show that the application of the BixSiyOz coating, imparts thermodynamic stability to the surface increasing the protection potential of the system 27,28 . Figure-7 shows the diffraction patterns, taken at an angle, for the coatings.…”
Section: Resultsmentioning
confidence: 74%
“…Measurements were made at 0, 720, 1440 and 2160 hours, respectively. The temperature was kept constant at 37 °C, to simulate the conditions of the human body, by immersing the electrochemical cell in a thermostatized bath circulator [30].…”
Section: Resultsmentioning
confidence: 99%
“…This posed a strenuous challenge to mankind and urged to discover a mechanically stabilized and biocompatible implant material. Physical vapour deposition (PVD), an eco-friendly technique has enabled the implant material to be coated with surface materials thereby strengthening the mechanical wear resistance [2]. In addition to this, a proper selection of coating material prompts brings about a good biocompatible implant material that is free from many health effects such as allergy, inflammation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The result reported that both the wear and corrosion resistance got enhanced with all three surface treatments. Guzman et al [2] evaluated the characteristics of micro-abrasive wear on the stainless steel coated with Ta–Hf–C/Au using PVD. A tremendous improvement in the micro-abrasive wear resistance for the coated specimen was notified.…”
Section: Introductionmentioning
confidence: 99%